Teacher Role and Domain of Expertise in the 21st Century: Evidence from Preservice Biology Teacher - Marlina*, Reni; Suwono, Hadi; Yuenyong, Chokchai; Ibrohim, Ibrohim; Hamdani, Hamdani (Universitas Syiah Kuala, 2024)
This research focuses on biology education students' perspectives regarding teacher roles and domains of expertise in the 21st century identified from micro teaching courses. The aimed of this study was to describe the types of teacher roles that emerge in teaching practice in micro teaching courses and identify domains of expertise based on the perceptions of prospective biology teacher students while attending micro teaching courses. This research method is a qualitative based on the lesson study framework. The research instruments used questionnaires, interviews, and the observation of the learning process. The research results show that there are weaknesses in the domain of expertise needed in the 21st century, which consists of mastery of content/material, technology and pedagogy. Suggestions for further research are that good cooperation between universities and partners in schools is needed by forming the lesson study for learning communities (LSLC). This LSLC can develop the competencies of prospective biology teacher students, especially those related to pedagogical, technological, and concept mastery competencies on an ongoing basis